Analisis Tarif Optimum Cukai Rokok - Himawan Yusuf; Adi Bowo Wijaya; Fuad Abdalla (Unit Penerbitan Politeknik Keuangan Negara STAN, 2023)
This study aims to analyze the optimum excise tariff for cigarettes and create tariff and consumption simulations to facilitate policymakers in determining top priorities, both health and income. The method used is quantitative method with the maximum tax revenue equation, with the research data being machine-rolled Kretek cigarettes class I from 2010 to 2022. The test results show that the squared variable of the excise rate has a negative coefficient and a significant result with a p-value of 0.0025. This shows that the excise tariff satisfies the maximum tax equation and based on the model, the optimum excise tax revenue is obtained when the tariff is Rp. 1,100.-. Based on the optimum rate, the simulation results show that when the excise rate is increased above 5% of the optimum rate, it can cause cigarette consumption to fall more than the rate increase, and when the rate is lowered above 5%, the increase in consumption is smaller than the decrease in the rate.